La construcción social del cuerpo sano. El estilo de vida saludable y de las prácticas corporales de la forma como exclusión - Vicente Pedra, Miguel (Nómadas. Critical Journal of Social and Juridical Science, 2010)
The article argues that the definitions of the health and the physical form are elaborated from a know-power space that responds to not neutral or universal conceptions of body. These definitions, given the social and cultural diversity in the developed world, provoke ideological and ethical questions with respect to the health policies and to the institutional propaganda around the bodily habits between which is the call to the modalities of physical practices generically denominated of the form. Using the constructivist and genealogical analysis, the objective it is to discover the relations between the conditions, accepted like neutral, of the denominated healthy lifestyle and the cultural, ideological and economics interests of the hegemonic social groups. In this respect, it is collected that knowledge and the practices that form this lifestyle and the image of the body in form are the product of the cultural schemes that these groups construct and they impose because they show major representation (numerical and of influence) of investigators and professionals in the social space.